2019
DOI: 10.1111/cea.13310
|View full text |Cite
|
Sign up to set email alerts
|

Variability of blood eosinophils in patients in a clinic for severe asthma

Abstract: Background: Blood eosinophils are used to determine eligibility for agents targeting IL-5 in patients with uncontrolled asthma. However, little is known about the variability of blood eosinophil measures in these patients before treatment initiation.Objective: To characterize variability and patterns of variability of blood eosinophil levels in a real-world clinic for severe asthmatics.Methods: Retrospective review of blood eosinophils measured over a 5-year period in patients enrolled in an urban clinic. Repe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 43 publications
(88 reference statements)
5
21
0
5
Order By: Relevance
“…8,9 Moreover, they offer theragnostic value by defining a phenotype of severe asthma patients that can be stratified towards newly emerged anti-IL5/ IL-5 receptor alpha (IL-5 Rα) therapies. [10][11][12][13] Eosinophilic inflammation is recognized to fluctuate in both blood and sputum over time [14][15][16][17] : few patients are 'eosinophilic' at every measurement. 18,19 This therefore challenges the robustness of translating associations determined by single-measurement crosssectional study designs, 20 into clinical practice, particularly when full blood counts are among the most commonly requested blood test panels in clinical care.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Moreover, they offer theragnostic value by defining a phenotype of severe asthma patients that can be stratified towards newly emerged anti-IL5/ IL-5 receptor alpha (IL-5 Rα) therapies. [10][11][12][13] Eosinophilic inflammation is recognized to fluctuate in both blood and sputum over time [14][15][16][17] : few patients are 'eosinophilic' at every measurement. 18,19 This therefore challenges the robustness of translating associations determined by single-measurement crosssectional study designs, 20 into clinical practice, particularly when full blood counts are among the most commonly requested blood test panels in clinical care.…”
Section: Introductionmentioning
confidence: 99%
“…We used blood biomarkers and FeNO to assess the inflammatory status of the patients. We, and others, have shown that blood biomarkers, including those for eosinophils, may be variable [ 76 ] and FeNO varies over time and control status.…”
Section: Discussionmentioning
confidence: 99%
“…However, little is known about the longitudinal variation in blood eosinophils in patients and their utility as a biomarker from a pragmatic real‐world clinic. Rakowski and colleagues have addressed this very important issue by reviewing variability in blood eosinophils measured over a 5‐year period 52 . Only 13/219 patients had a blood eosinophil count consistently above 300 cells/mcl.…”
Section: Asthma and Allergic Rhinitismentioning
confidence: 99%